Inconsistent clinical outcomes following afatinib treatment in NSCLC patients harboring uncommon epidermal growth factor receptor mutation - Dong, Wei; Wang, Congjie; Wang, Chunsheng; Zhao, Kewei; Ma, Zhao; Hu, Shanliang (Frontiers in Oncology, 2022)
Abstract Background: Uncommon epidermal growth factor receptor (EGFR) mutations consist of a heterogeneous population of molecular alterations, and the available clinical data on the outcomes of patients with non-small-cell lung cancer (NSCLC) harboring uncommon EGFR mutations following afatinib treatment are limited. The purpose of this pooled analysis was to investigate the clinicopathological features of patients with uncommon EGFR mutations (um-EGFRms) along with their treatment response and survival outcomes following afatinib treatment. Methods: We performed a literature search in the NCBI PubMed database to identify relevant articles and conducted this pooled analysis based on 70 studies. The relationships between patient clinical characteristics, EGFR mutation type and the response to afatinib treatment were analyzed using univariate chi-square analysis, and survival analysis was performed using the Kaplan–Meier method. Results: Data from a total of 99 patients were included in the pooled analysis. The objective response rate (ORR) to treatment with afatinib was53.5%, with a median progression-free survival (mPFS) of 9.0 months. For patients administered first-line afatinib treatment, the ORR and median PFS were 73.5% and 15.6 months, respectively, which were both superior to those of patients treated with second- or later-line treatments (ORR:37.0%, p < 0.001; mPFS: 6.0months, p = 0.001). Moreover, patients with a single um-EGFRm were more likely to have a favorable response and prognosis benefit after treatment with afatinib than patients with multiple one (ORR: 63.3% vs 38.5%, p=0.017; mPFS: 15.6 months vs 6.0 months, p=0.010). Moreover, single um-EGFRm were independent predictive factors for better treatment response and superior PFS. Subgroup analysis indicated that patients harboring major um-EGFRms (i.e., L861Q, G719X, and S768I) exhibited the best treatment responses and prognoses (ORR: 74.1%, mPFS: 15.6 months), by contrast, patients harboring multiple um-EGFRms comprising 19del/L858R had the worst treatment responses and prognoses (ORR: 23.5%, mPFS: 5.6months). Conclusions: Patients with um-EGFRms exhibit favorable but inconsistent responses and survival outcomes following afatinib treatment, which closely related to the mutation pattern and cooccurring partner mutant genes. Administering afatinib for the treatment of patients with um-EGFRm might be considered an effective treatment option in some circumstances, but this recommendation requires further clinical studies for verification.